Distribution methods of Chinese vehicles in the Pacific Alliance countries (2021)
When the Chinese automotive industry decided to expand into the western market, it had to evaluate the best alternative for marketing its brands in the segmented and selected markets, including the countries that form the Pacific Alliance. This article, based mainly on secondary sources, develops, on the one hand, through a conceptual approach, the distribution methods implemented by automotive brands in general, and on the other hand, through an applied approach, the distribution strategies of the four Chinese brands that were selected —Changan, Great Wall, JAC, and BAIC— in the markets of Chile, Colombia, Mexico, and Peru.